Perancangan Aplikasi Penentuan Produksi Karet Pada PTPN 3 Kebun Sei Silau Dengan Menggunakan Metode Fuzzy Mamdani - Wanayumini Wanayumini; Devy Pratiwi (Universitas Asahan, 2018)
Abstract - This web application makes it easy for admin to handle rubber production without manually doing a tester. Good rubber production based on fuzzy mamdani is: Heat temperature with a value of -0.6 °, with rubber droplet conditions that are good for the production process. Dry air humidity with a value of -0.4%, with rubber droplets that are good for the production process. Intensity Dark light with a value of 0, rubber droplet conditions that are good for the production process. System decision support system that determines a decision to manage and analyze the work clearly. There are several things that weaken the competitiveness of rubber production including rubber processing is still done simply or manually, with the application of the Fuzzy Mamdani Method is expected to increase rubber production. Keywords - Rubber, Decision Support System, Fuzzy Mamdani Method